Designing environmental campaigns by using agent-based simulations: Strategies for changing environmental attitudes. - Mosler, Hans-Joachim; Martens, Thomas (Journal of Environmental Management, 2008)
Agent-based computer simulation was used to create artificial communities in which each individual was constructed according to the principles of the elaboration likelihood model of Petty and Cacioppo [1986. The elaboration likelihood model of persuasion. In: Berkowitz, L. (Ed.), Advances in Experimental Social Psychology. Academic Press, New York, NY, pp. 123-205]. Campaigning strategies and community characteristics were varied systematically to understand and test their impact on attitudes towards environmental protection. The results show that strong arguments influence a green (environmentally concerned) population with many contacts most effectively, while peripheral cues have the greatest impact on a non-green population with fewer contacts. Overall, deeper information scrutiny increases the impact of strong arguments but is especially important for convincing green populations. Campaigns involving person-to-person communication are superior to mass-media campaigns because they can be adapted to recipients' characteristics. Copyright (c) 2008 Elsevier Ltd.